Unveiling Betulinic Acid as a Potent CDK4 Inhibitor for Cancer Therapeutics - El-Gamal, Basiouny; A-Elgadir, Thoraya; Patel, Ayyub Ali; Ellatif, Mohamed Abd; Nasif, Khalid Ali; Alsamghan, Awad Saeed; Malik, Arshi; Elrouf, Mohamed Babiker Abd; Alghawanmeh, Imad; Saeed, Marwa; Ahmed, Osama Haroun; Makki, Soha; et al. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background CDK4 play a pivotal role in cell cycle regulation, making it a critical players in the development and progression of cancer. In recent years, there has been a growing interest in targeting CDK4 for cancer therapeutics, with a focus on the identification and development of small molecule inhibitors. Materials and Methods This work, using a strong in silico and in vitro methodology, reveals Betulinic Acid’s inhibitory efficacy against CDK4 for cancer therapy. Betulinic Acid, a pentacyclic triterpenoid with a variety of characteristics, has emerged as a promising CDK4 inhibitor. Results The study identifies key CDK4 binding sites using high-resolution structural modeling and cavity detection. Betulinic Acid’s highest fitness and predicted binding affinity were found, supporting its drug-likeness properties. Its pharmacokinetic viability, biological properties, and cytotoxicity assays show its concentration-dependent effects on cancer cells (A549 and NCI-H460). Molecular-level validations reveal a significant decrease in CDK4 mRNA expression and kinase activity, reinforcing its potential as a CDK4 inhibitor. Conclusion In conclusion, this comprehensive study bridges structural insights with experimental validations, positioning Betulinic Acid as a promising therapeutic agent for CDK4 inhibition in cancer, particularly lung cancer. The findings contribute significantly to drug discovery, paving the way for further preclinical and clinical investigations in the quest for effective cancer treatments.
Keywords: Betulinic Acid; Cancer therapeutics; CDK4 inhibition; Lung cancer treatment; Molecular docking; Pharmacokinetic viability